Preferences For Health Information and Participation in Decision Making: The Patients’ Perspectives for Hospital Improvement - Tamano, Norhaynee D.; Bacarisas, Joan P.; Picardo, Resty L.; Napoles, Jake C. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Patients of varying generations demand varying approaches. Additionally, hailing from diverse indigenous cultures and religions, they have distinct historical backgrounds that shape their personal qualities. In healthcare, holistic care is critical, and it must meet the dynamism and constant change of the world, while also taking generational gaps into account as a major concern in healthcare. This quantitative research made use of the descriptive, comparative (non-causal) design to compare the differences in the perceptions on the preferences for health information and participation in decision making among generational in-patients in a government-retained hospital for the 2nd quarter of 2021. Findings of the study revealed that the respondents had a good preference on health information on diagnosis, treatment, laboratory tests, self-care, and psychosocial while they are only had a fair preference of health information on complimentary or alternative medicine and healthcare provider. The Generation Z scored the highest of the four generations while the Baby Boomers scored the lowest. The respondents had a poor preference for participation in decision making on their diagnosis and treatment. They had a fair preference for participation in decision making on their laboratory tests but they had a good preference for participation in decision making on their self-care, complimentary or alternative medicine, and healthcare provider. They had a very good preference for participation in decision making on the psychosocial factors. The Baby Boomers scored the highest of the four generations, while the Generation Z scored the lowest. There was a significant difference in the perceptions on preference on health information. The Generation Z had a better preference on health information as compared to the Baby Boomers. Further, there was a significant difference in the perceptions for participation on decision making. The Baby Boomers, the Generation X, and the Generation Y are much better in terms of the perception of preferences for participation in decision making over the Generation Z. With the findings, a multi-generational health information and decision-making enhancement plan was created.